2009
DOI: 10.1017/s0967199409005504
|View full text |Cite
|
Sign up to set email alerts
|

In vitrodevelopment of goat parthenogenetic and somatic cell nuclear transfer embryos derived from different activation protocols

Abstract: Oocyte activation is an essential step in animal cloning to allow subsequent development of the reconstructed embryos. A special activation protocol is required for different animal species. The present study investigated low temperature, electrical pulses, ethanol, ionomycin and strontium for goat oocyte activation in order to optimize the protocols. We found, as a result, effective activation and parthenogenetic development of goat oocytes that had been derived from ionomycin, strontium and electrical pulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Although no sign of cleavage and further development was observed when these oocytes were left intact for 48 h, evidence from nuclear staining (Fig. 1G) in accordance with additional evidence (Chen et al, 2007;Guo et al, 2010) convinced us that these apparently MII oocytes would be more precisely considered as AII-TII oocytes.…”
Section: Metaphase II or Anaphase Ii-telophase Ii Oocytes?supporting
confidence: 63%
See 1 more Smart Citation
“…Although no sign of cleavage and further development was observed when these oocytes were left intact for 48 h, evidence from nuclear staining (Fig. 1G) in accordance with additional evidence (Chen et al, 2007;Guo et al, 2010) convinced us that these apparently MII oocytes would be more precisely considered as AII-TII oocytes.…”
Section: Metaphase II or Anaphase Ii-telophase Ii Oocytes?supporting
confidence: 63%
“…They could show that goat oocytes would be appropriately parthenogentically activated if treated with a decreased concentration of ionomycin (2.5 mM) and duration of ionomycin (1 min) and DMAP (2 h). In the literature, five additional indications conclude that reconstructed oocytes and particularly zonafree reconstructed goat oocytes require a more specific activation protocol: (1) caprine-matured oocytes possibly endure a spontaneous activation and progress toward the AII-TII stage (Chen et al, 2007;Guo et al, 2010), (2) SCNT oocytes are routinely activated 27-30 h postmaturation when oocytes are aged, and due to reduction in the levels of MPF and MAPK activity, activation triggering threshold reduces, (3) enucleation decreases MPF and MAPK level of the oocytes (Lee and Campbell, 2006), (4) electrofusion of reconstructed oocytes primarily activate oocytes (Loi et al, 1998), and (5) zona-free oocytes are more sensitive and responsive to artificial activation than zona-intact ones (Vajta et al, 2003). Accordingly, in Experiment 3 it was observed that initial activation by EP, 1-min exposure with 5 mM ionomycin, and then incubation with DMAP for either 2 or 4 h resulted in the highest blastocyst development.…”
Section: Parthenogenetic Activation Of Zona-free Oocytesmentioning
confidence: 99%
“…The authors would like to express their gratitude to the Royan Institute for their full support. Guo et al, 2010, Köhler et al, 2008 …”
Section: Acknowledgementsmentioning
confidence: 99%
“…In both shipped and non shipped oocytes, parthenotes developing from ionomycin and ethanol activated oocytes had significantly greater blastocyst development compared to IVF embryos. Guo et al [94] evaluated the ionomycin, strontium and electrical pulse for the effecttive activation and parthenogenetic development of goat oocytes. The activation of oocytes by ionomycin combined with 6-dimethylaminopurine, strontium plus cytochalasin B and electrical pulses combined with cytochalasin B revealed 79.3% -81.6%, 2.2% -78.8% and 65.5% of the oocytes cleaved and 16.2% -24.8%, 0% -15.6% and 11.1% of the cleaved embryos developed into blastocysts, respectively.…”
Section: Parthenogenesismentioning
confidence: 99%